Komplikationen der Leberzirrhose – medikamentöse versus interventionelle Therapie - Sturm, Lukas; Rössle, Martin; Schultheiß, Michael (DMW - Deutsche Medizinische Wochenschrift, 2019)
The prognosis of patients with liver cirrhosis is impaired by complications such as variceal bleeding, ascites, hepatorenal syndrome, hepatic encephalopathy and hepatocellular carcinoma. A steadily increasing array of treatment options for these complications is available, including pharmaceutical treatment (e. g. beta blockers for varices or diuretics for ascites), endoscopic treatment (e. g. band ligation of varices), radiological interventions (e. g. transjugular shunt, transarterial chemoembolization) and liver transplantation. Most of the complications occur due to portal hypertension. Therefore, decompressive treatment by implantation of a transjugular intrahepatic portosystemic shunt (TIPS) an effective therapeutic option for many complications of liver cirrhosis. Its main indications are acute and recurrent variceal bleeding in patients with advanced disease as well as refractory ascites. The TIPS does not affect options of abdominal surgery and may therefore be used as a bridge to liver transplantation.
Keywords: Leberzirrhose; Aszites; Varizenblutung; transjugulärer intrahepatischer portosystemischer Shunt